2010
DOI: 10.1007/s00455-010-9312-2
|View full text |Cite|
|
Sign up to set email alerts
|

Silent Aspiration Risk is Volume-dependent

Abstract: Clinical swallow protocols cannot detect silent aspiration due to absence of overt behavioral signs, but screening with a much larger bolus volume, i.e., 90 cc vs. 1-10 cc, may elicit a reflexive cough in individuals who might otherwise exhibit silent aspiration. A swallow screen that maintains high sensitivity to identify aspiration risk while simultaneously reducing the false-negative rate for silent aspiration would be beneficial. The purpose of this study was to investigate whether silent aspiration risk w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
54
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 48 publications
3
54
0
3
Order By: Relevance
“…6,63 We were surprised by the omission of silent aspiration data as an outcome of the reference test related to the WST in the peer-reviewed studies included in this review, especially when this clear limitation of WSTs may result in false negatives leading to aspiration pneumonia. Although silent aspiration risk may be dependent on the volume of water presented to the patient, 64 more research is needed to validate this theory. Adverse events and outcomes from missing silent aspiration on screenings are beginning to emerge.…”
Section: Discussionmentioning
confidence: 99%
“…6,63 We were surprised by the omission of silent aspiration data as an outcome of the reference test related to the WST in the peer-reviewed studies included in this review, especially when this clear limitation of WSTs may result in false negatives leading to aspiration pneumonia. Although silent aspiration risk may be dependent on the volume of water presented to the patient, 64 more research is needed to validate this theory. Adverse events and outcomes from missing silent aspiration on screenings are beginning to emerge.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, cases in which food, regardless of the amount, passed the vocal cords and entered the trachea with no coughing were considered to be silent aspiration. However, Leder et al reported that silent aspiration is affected by the amount of aspiration [16]. There are also patients in whom coughing is considerably delayed, so a definition of silent aspiration that includes the time from aspiration until coughing is needed.…”
Section: Silent Aspirationmentioning
confidence: 99%
“…Further research incorporated a basic cognitive assessment [5] and oral mechanism evaluation resulting in a 3-ounce water swallow challenge protocol that has the additional advantages of reliably and safely identifying patients with aspiration risk and successfully recommending specific oral diets for different patient populations, i.e., trauma patients [6], general acute care inpatients [7], and patients with acute stroke [8]. The protocol's strengths include prospective, consecutive, and referral-based population samples that span the age range [9].We are grateful for this opportunity to clarify the misunderstanding that patients were excluded from the 3-ounce water swallow challenge due to safety issues [1]and we take umbrage at the suggestion that patients were excluded in the initial study [2] but not reported.All patients were tested with 3 ounces of water regardless of fiberoptic endoscopic evaluation of swallowing (FEES) results [2,3]. Only during FEES were 313 participants deemed unsafe to be given thin liquid and 110 participants were deemed unsafe to be given puree but all still participated in the 3-ounce water swallow challenge.…”
mentioning
confidence: 99%
“…
Daniels[1] has raised a number of issues relevant to our 3-ounce water swallow challenge study [2] and specifically to silent aspiration risk is volume-dependent [3]. We welcome the opportunity to clarify the issues.

We were not the first to report on the utility of the 3-ounce water swallow test [4].

…”
mentioning
confidence: 99%